Longitudinal performance trajectories of young female sprint runners: a new tool to predict performance progression - Romann, M.; Javet, M.; Hernandez, J.; Heyer, L.; Trösch, S.; Cobley, S.; Born, D.,P. (Frontiers in Sports and Active Living, 2024)
Background: Longitudinal performance tracking in sports science is crucial for accurate talent identification and prognostic prediction of future performance. However, traditional methods often struggle with the complexities of unbalanced datasets and inconsistent repeated measures.